2023
DOI: 10.1126/sciadv.abq8421
|View full text |Cite
|
Sign up to set email alerts
|

Testing, explaining, and exploring models of facial expressions of emotions

Abstract: Models are the hallmark of mature scientific inquiry. In psychology, this maturity has been reached in a pervasive question—what models best represent facial expressions of emotion? Several hypotheses propose different combinations of facial movements [action units (AUs)] as best representing the six basic emotions and four conversational signals across cultures. We developed a new framework to formalize such hypotheses as predictive models, compare their ability to predict human emotion categorizations in Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…While many prior studies have evaluated facial action unit (AU) differences in relation to pain in controlled settings 46,47 , we found that facial expression changes underlying self-reported pain states had little overlap with conventionally reported pain-related AUs. Instead, these AUs (AU14, AU15, AU26) may reflect more general changes in affect 48 . In contrast, facial expressions associated with momentary pain exhibited many of the canonical pain-related AUs (AU5, AU6/7, AU9/10, AU11/12, AU25/26), suggesting immediate pain onset.…”
Section: Discussionmentioning
confidence: 99%
“…While many prior studies have evaluated facial action unit (AU) differences in relation to pain in controlled settings 46,47 , we found that facial expression changes underlying self-reported pain states had little overlap with conventionally reported pain-related AUs. Instead, these AUs (AU14, AU15, AU26) may reflect more general changes in affect 48 . In contrast, facial expressions associated with momentary pain exhibited many of the canonical pain-related AUs (AU5, AU6/7, AU9/10, AU11/12, AU25/26), suggesting immediate pain onset.…”
Section: Discussionmentioning
confidence: 99%
“…Facial expressions of humans can be classified into two types based on the methods used for emotion recognition: rule-based and machine learning-based. The first approach employs predefined rules and features to recognize and reproduce human facial expressions ( Snoek et al, 2023 ). It relies on expert-defined rules and models to infer emotional states by calculating facial features such as eye shape, mouth movement, and eyebrow position, as well as vocal features like intonation and speech rate.…”
Section: Progress In the Application Of Brain-machine Interfaces In T...mentioning
confidence: 99%
“…2. Accounting for Individual Differences: It is acknowledged that different individuals may use different compositions of facial AUs to perceive the same emotion 47,48 . To preserve such individual differences, the methodological and analytical approaches must be able to discern the specific AUs that each participant utilizes to perceive each emotion, instead of assuming what these AUs are, or building an average that represents no one.…”
Section: Introductionmentioning
confidence: 99%